ICPES 2019 Selected articles from the 9th International Conference on Power and Energy Systems, Perth, Australia - Shahnia, Farhad; Deilami, Sara.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2020)
This book highlights various applications of renewable energy systems and their enabling technologies in electrical power systems. It features selected articles from the 9th International Conference on Power and Energy Systems (ICPES 2019), held in Perth, Australia, which presented the latest advances in the field and provided a platform to exchange ideas and foster future collaboration with a sustainable future in mind.
Blockchain Integrated Secured Scenarios in Advanced Wireless Networks -- Docker functioning in cloud Infrastructure -- A Review Of Meta-heuristic Techniques For Solving University Course Timetabling Problem -- Using Latent Dirichlet Allocation with Automated Content Analysis to predict Engagement for Social Media Influencers -- Smart Heart Attack forewarning Model Using MapReduce Programming Paradigm -- Tuning of CNN Architecture by CSA for EMNIST Data -- Efficient Emergency Message DHC Broadcasting in Vehicular Ad hoc Networks.
Keywords: Electric power production; Renewable energy sources; Sustainability; Cooperating objects (Computer systems).; Energy policy; Energy and state; Electrical Power Engineering; Renewable Energy; Sustainability; Cyber-Physical Systems; Energy Policy, Economics and Management